The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/ma16020536
|View full text |Cite
|
Sign up to set email alerts
|

Subthreshold Laser Ablation Measurements by Langmuir Probe Method for ns Irradiation of HfO2 and ZrO2

Abstract: The unbiased Langmuir probe (LP) method was used to perform measurements on HfO2 and ZrO2 samples around the laser ablation threshold on a wide range of irradiation conditions. Important changes in the lifetime (from ms to μs) and the shape of the charge particle current were seen with the increase of the laser fluence. The ablation threshold was estimated by evaluating the overall average ablated charge as a function of the laser fluence. Above the ablation threshold, the generation of high kinetic species is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In our previous work [ 20 ] , we have shown that LP signal can be used to quantify the ablation threshold value by using the average current representation as a function of the laser fluence. Here we expand the procedure by analyzing the variation of the ejected charge (Figure 4(a)) and the sample compensation charge (Figure 4(b)) as a function of laser fluence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work [ 20 ] , we have shown that LP signal can be used to quantify the ablation threshold value by using the average current representation as a function of the laser fluence. Here we expand the procedure by analyzing the variation of the ejected charge (Figure 4(a)) and the sample compensation charge (Figure 4(b)) as a function of laser fluence.…”
Section: Resultsmentioning
confidence: 99%
“…The scenarios for material removal from the target follow a complex interconnectivity of electrostatic and thermal mechanisms, which are temporally and spatially separated: the first stages of laser ablation are of an electrostatic nature, while the second stages are of a thermal nature. In our previous work [ 20 ] , we have shown that the Langmuir probe (LP) is a suitable technique for estimating the nanosecond ablation threshold limit as it detects contributions from each stage [ 21 ] . Other reports focus on LP measurements of ablation threshold in the ns regime [ 22 ] , while reports on the detection of the fs-incubation stage emphasize the necessity of having a minimum of 10,000 pulses to estimate the threshold [ 23 ] .…”
Section: Introductionmentioning
confidence: 99%